SACCOS and Women’s Poverty Reduction In Morogoro District, Tanzania - Assenga, Emiliana; Mwageni, Eleuther; Kayunze, Kim (Tanzania Journal for Population studies and Development, 2013)
This paper intends to look at the role of SACCOS in poverty reduction using data from a research done in 2007 to a sample of 120 women in Morogoro District, Tanzania. The specific objectives of the research were to calculate income from income-generating activities (IGAs); compare income earned per month between women in SACCOS and their counterparts who were not in SACCOS; determine wealth status based on assets owned; and compare poverty levels between SACCOS members and non-SACCOS members. The study revealed that income of women SACCOS members was three times that of non-SACCOS members, implying the effectiveness of credit on poverty reduction. Besides, results of a t-test showed significant differences in the incomes (p = 0.000) between members and non-members. This led to the conclusion that SACCOS have improved women’s living standards. The study recommends that formal, semi-formal, and informal micro-financial institutions and individual money lenders should continue giving credit to poor women, while improving their schemes to bring more positive impact. In addition, credit providers need to review their policies on the amount of credit provided and interest rate so as to increase the number of women getting credit for IGAs. Moreover, women should be encouraged to join SACCOS, and SACCOS dealing with women should be supported by financial institutions and policy makers.